Cegah Stunting: Indonesia Tumbuh Sehat dan Hebat Desa Jogoyitnan, Kecamatan Wonosobo, Kabupaten Wonosobo - Nugroho, Adhi Wahyu; Puji Hartono, Febrian Rizki; Perwitosari, Warih; Widhianingrum, Wahyu Astri (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Abstract Introduction: Thematic KKN is an academic activity with a clear theme and program. This activity partner aligns research and community service programs with internal and external funds. KKN activities were carried out in Jogoyitnan Village, Wonosobo District, Wonosobo Regency with the theme "Prevent Stunting, Healthy My Country, Grow Great My Indonesia" from October 27 - November 11, 2023.. Objective: The purpose of this service was raising awareness of the importance of knowledge about stunting in the target community. Method: This public service was conducted by Awareness campaign on stunting in the community, Nutrition and health counseling for pregnant women and nursing mothers, Supplementary feeding program for children under five with stunting risk, Training on making nutritious food menus and pharmaceutical products for pregnant women and children under five. Result: The results of this community service are increased awareness and knowledge of the target community regarding the importance of stunting prevention, the target community is able to make food and pharmaceutical products that can support nutritional needs from an early age, increased knowledge of the target community regarding the importance of using, storing and destroying pharmaceutical products. Conclusion: The importance of knowledge about stunting by the community can reduce the incidence of stunting, nutritious food for toddlers can reduce the risk of children becoming stunted and the need for people to know Get-Use-Save-Waste medicine (DAGUSIBU) to maintain family health.